Among the trees. - Rugoff, Ralph, 1957-; Cripps, Phoebe; Guggenheim, Katie; Carrier, Marie-Charlotte; Biddle, Lucy Hughes; Hayward Gallery (London : Hayward Gallery Publishing, 2020)
"'Among the trees' brings together more than 30 international artists whose works explore our relationships with trees and forests. Beginning with pioneering works from the late 1960s - a decade that saw the emergence of the modern environmental movement - 'Among the trees' surveys a remarkably expansive artistic terrain. It invites us to consider trees as symbols and living organisms that have shaped human civilisation, and to celebrate their enduring resonance as a source of inspiration for some of the most compelling artists of our time" - back cover.
Artists include: Robert Adams, Eija-Liisa Ahtila, Yto Barrada, Johanna Calle, Gillian Carnegie, Tacita Dean, Peter Doig, Jimmie Durham, Kirsten Everberg, Anya Gallaccio, Simryn Gill, Rodney Graham, Shi Guowei, Hugh Hayden, Eva Jospin, Kazuo Kadonaga, William Kentridge, Toba Khedoori, Luisa Lambri, Myoung Ho Lee, Zoe Leonard, Robert Longo, Sally Mann, Steve McQueen, Jean-Luc Mylane, Mariele Neudecker, Virginia Overton, Roxy Paine, Giuseppe Penone, Abel Rodriguez, Ugo Rondinone, George Shaw, Robert Smithson, Jennifer Steinkamp, Thomas Struth, Rachel Sussman, Pascale Marthine Tayou, Jeff Wall.
Published on the occasion of an exhibition held at the Hayward Gallery, London, UK, 4 March to 17 May 2020.
Keywords: Trees in art -- Exhibitions; Landscape photography -- Exhibitions